Comparative Effects of Fixation and Storage on Bone Tetracycline Fluorescence - Arighi, M.; Wilson, J. W. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
As an adjunct to an ongoing project, ends of longbones, including the growth plate, were collected from tetracycline labelled immature rabbits and calves. Samples were stored from a few days up to two months at room temperature, refrigerator temperature (+4°C), –20°C, or –70°C, and unfixed, formalin-fixed or alcohol-fixed. Qualitative and quantitative aspects of cut sections were evaluated. Freezing resulted in the least alteration. Fixed bone samples (alcohol or formalin) all progressively discoloured with increasing storage. Comparison between fresh, stored and differently fixed sections did not identify any change in the measured distance between labels; though the clarity of the labels was affected. Formalin fixation and storage did not result in mark degradation nor alteration of the labels.Tetracycline fluorescence, in labelled growth plates, was evaluated following storage from a few days up to two months at various temperatures and unfixed, formalin-fixed or alcohol-fixed. Neither the method of storage nor the fixative effected the measured distance between sequential labels in specimens. Fixed bone samples all discoloured with increasing storage. Previous literature alluded to problems with formalin fixation could not be substantiated in this study.
Keywords: Tetracycline; fluorescence; bone; storage; freezing; formalin; alcohol